2011
DOI: 10.1002/cncr.26378
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intravesical and oral administration of 5‐aminolevulinic acid in the clinical benefit of photodynamic diagnosis for nonmuscle invasive bladder cancer

Abstract: BACKGROUND: This study was undertaken to evaluate the clinical value of photodynamic diagnosis (PDD) with intravesical and oral instillation of 5-aminolevulinic acid (ALA) (ALA-PDD), and transurethral resection of bladder tumor (TURBT) guided by ALA-PDD (PDD-TURBT) for nonmuscle invasive bladder cancer. METHODS: Of all 210 cases, 75 underwent PDD with intravesically applied ALA, and 135 cases underwent PDD with orally applied ALA. Diagnostic accuracy was evaluated by comparing the level on images of ALA-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 41 publications
1
74
1
2
Order By: Relevance
“…PpIX has another property, which is its accumulation in tumor cells, and augmented red fluorescence results in the identification of tumor cells. Its emission of red fluorescence and accumulation in tumor cells are fundamental for PDD [16][17][18].…”
Section: Tumor Cells and Ppix Accumulationmentioning
confidence: 99%
“…PpIX has another property, which is its accumulation in tumor cells, and augmented red fluorescence results in the identification of tumor cells. Its emission of red fluorescence and accumulation in tumor cells are fundamental for PDD [16][17][18].…”
Section: Tumor Cells and Ppix Accumulationmentioning
confidence: 99%
“…Currently, in Western countries, PDD by transurethral administration of a hexalated form of 5-ALA, 5-ALA hexyl ester (HAL), is performed as a routine medical practice. In Japan, Inoue et al [10] initiated a clinical study on the usefulness of 5-ALA in 2004, and obtained the outcome similar to those in studies performed overseas. Based on this our previous clinical study, we planned an investigator-initiated clinical trial with the aim of acquiring pharmaceutical approval.…”
Section: Introductionmentioning
confidence: 72%
“…The agent was approved for sale as an internal diagnostic drug for malignant glioma surgery in 2007 by the European Medicine Agency and in 2013 by Pharmaceuticals and Medical Device Agency in Japan where Nobelpharma and SBI Pharmaceuticals sell this agent for malignant glioma [10]. Based on these findings and in consideration of safety, 20 and 10 mg/kg were set to investigate the optimum dose for Japanese patients.…”
Section: Investigational Agentmentioning
confidence: 99%
“…Inoue et al [14] reported that the use of oral 5-ALA is just as effective as intravesical instillation.…”
Section: Photosensitisermentioning
confidence: 99%